Pengaruh KeteladananOrangtua Terhadap Perilaku Keagamaan Anak PadaSiswa Kelas V Sdn Paketiban 02 Kecamatan PangkahKabupaten Tegal 2016 - Bekhi, Okta Maizar (2016)
This study aims to: (1) Determine The Effect Of Parents Against Religious Behavior Modeling Kids In Class V Students Of SDN 02 Paketiban Pangkah District Of Tegal. This type of research is descriptive quantitative research. This study was conducted in 02 primary schools paketiban pangkah district of tegal. The population in this study is a class V. The samples used were fifth grade students of academic year 2014/2015, amounting to 30 students. Data collection techniques such as questionners, interviews, and documentation. The analysis technique used is a sample linear regression techniques, t test, F test, and the test of determination. Based on the research results indicate that the linear regression equation as follows = 35.332 + 0.625 X, based on the equation shown that the reggression coefficient independen variable - value positive, meaning that based on the research can be said the higher ideals of parents will be higher religious behavior and vice versa. After a simple reggression analysis followed by F test based on testing known that nil F hittung F>F table, ie 24.294>4.15 and significant value <0,05 exemplary 0,000. This means parents exemplary effect on religious behavior in class V students of SD Negeri 02 paketiban academic year2014/2015. Results of determination coefficient obtained at 0,447, the meaning of this coefficient is that the influence exerted by the variable exemplary religious behavior of parents of fifth grade students in elementary school paketiban 02 year 2014/2015 amounted to 44.7%, while 55.3% are influenced by other variables. After determine the influence of independent variables on the dependent variable then followed by t count>t table, ie 44.929>2.037 and significant value <0.05, namely variable exemplary 0,000. Mean is that parents significantly influence the religious behavior fifth grade students in elementary school state paketiban 02 of the school year 2014/2015.